Redesain Pusat Konservasi Dan Edukasi Penyu Di Desa Serangan, Bali: Bahasa Indonesia - Pramantya Narayana; I Kadek Mertawijaya; I Wayan Gede Suacana (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
Serangan Village is located in South Denpasar District, Serangan village is one of the areas that has potential marine resources. Turtles are animals that are beneficial to human life, if bred. These benefits include aspects of increasing economic growth through the fisheries sector, maintaining the balance of the ecosystem chain, science, developing educational tourism. The Turtle Conservation and Education Center is an effort for coastal communities in Serangan Village as an educational medium on the community's role in maintaining and protecting the turtle habitat ecosystem in Serangan Village. This turtle conservation was formed to save turtles from slaughter, trade and consumption by local people due to constraints and adaptation strategies in different seasons. At the turtle conservation and education center there are several problems, namely: the zoning system, space layout, circulation, obsolete buildings, and inadequate building materials that need to be redesigned to meet the needs of visitors. This design applies the concept of Nature In Space and applies the theme of biophilic This redesign applies the concept of Nature In Space which means nature in space with the Biophilic Architecture Theme so that visitors who come can reduce stress and feel comfortable in this facility.